Contemporary Processes of Concentration and Specialization of Industrial Activity in Post-Socialist States as Illustrated by the Case of Wrocław and Its Suburbs (Poland) - Dominik Sikorski (MDPI AG, 2021)
This paper explores the issues of contemporary spatial differentiation in the process of industry concentration and the accompanying specialization according to the intensity of research and development in urban agglomerations, as exemplified by Wrocław and its suburbs. The aim of the study was to assess the degree and directions of advancement of these processes and to identify spatial patterns in the location and relocation of industry operators in the analyzed area. The industrial location was analyzed on the basis of industry operators registered in section C (industrial processing) according to the Polish Classification of Activities (PKA) in city districts in 2008 and 2016. The industry’s spatial structures were presented using the classification of industrial processing according to R&D intensity broken down into high-, medium-high-, medium-low-, and low-tech industry sectors. Quantitative methods were used to analyze and identify the degree of spatial concentration and specialization of the industry. The underlying analytical statistics included relative indicators, such as the location quotient (LQ), Florence’s location quotient, or the Krugman Specialization Index, as well as analyses of market structures (Herfindahl–Hirschman index or discrete index). The findings of this research revealed quite significant changes taking place in the internal spatial structure of Wrocław and its immediate vicinity in terms of the industry concentration and specialization. This phenomenon was much more dynamic and turbulent in the post-socialist countries than in the cities of Western Europe. Likewise, Wrocław and its suburban zone are characterized by a significant diversification and intensity of the processes subject to this analysis. These processes proved to be complex and selective.